2023
DOI: 10.1038/s41440-023-01271-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association of hypertension and dyslipidemia with cognitive function in community-dwelling older adults: the SONIC study

Abstract: The associations among cognitive function, hypertension, and dyslipidemia in older adults are controversial. Therefore, we investigated the associations among cognitive decline, hypertension, dyslipidemia, and their combination in community-dwelling older people in their 70s, 80s, and 90s in the long-term observational Septuagenarians, Octogenarians, Nonagenarians, Investigation with Centenarians (SONIC) study. We administered the Montreal Cognitive Assessment Japanese version (MoCA-J) by trained geriatricians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Our findings are partially supported by other studies that reported inverse associations between BP levels and cognitive function in very old adults. Nakamura et al ( 6 ) found that high BP was a predictor of better global cognitive function 3 years later in a cohort of very old Japanese adults. Similar results were reported by Corrada et al ( 7 ) and Chen et al ( 26 ) after examining North American and Japanese older adults aged 90 years and older, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are partially supported by other studies that reported inverse associations between BP levels and cognitive function in very old adults. Nakamura et al ( 6 ) found that high BP was a predictor of better global cognitive function 3 years later in a cohort of very old Japanese adults. Similar results were reported by Corrada et al ( 7 ) and Chen et al ( 26 ) after examining North American and Japanese older adults aged 90 years and older, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for these findings is that high BP might be a compensatory mechanism to maintain adequate cerebral perfusion in the face of vascular detriments caused by aging ( 6–9 ). Indeed, the old vessel is commonly characterized by losses in structural integrity and function, which involves significant impairment of endothelium dilation, resulting in reduced blood flow to major tissues, including the brain ( 28–30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study by Nakamura et al [1] is valuable for understanding the associations among cognitive decline, hypertension, and dyslipidemia in older adults. The Septuagenarians, Octogenarians, Nonagenarians, Investigation with Centenarians (SONIC) study provides important insights into these complex relationships.…”
mentioning
confidence: 80%